Optimizing CRE and PhiC31 mediated recombination in Aedes aegypti - Carabajal Paladino, Leonela Z.; Wilson, Ray; Tng, Priscilla Y. L.; Dhokiya, Vishaal; Keen, Elizabeth; Cuber, Piotr; Larner, Will; Rooney, Sara; Nicholls, Melanie; Uglow, Anastasia; Williams, Luke; Anderson, Michelle A. E.; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
This is a provisional file, not the final typeset article Genetic manipulation of Aedes aegypti is key to developing a deeper understanding of this insects' biology, vector-virus interactions and makes future genetic control strategies possible. Despite some advances, this process remains laborious and requires highly skilled researchers and specialist equipment. Here we present two improved methods for genetic manipulation in this species. Use of transgenic lines which express Cre recombinase allowed, by simple crossing schemes, germline or somatic recombination of transgenes, which could be utilized for numerous genetic manipulations. PhiC31 integrase based methods for site-specific integration of genetic elements was also improved, by developing a plasmid which expresses PhiC31 when injected into early embryos, eliminating the need to use costly and unstable mRNA as is the current standard.